Self Financing Technical Institutions-A Unified Policy - Rao, Y. V. N. (Journal of Engineering Education Transformations, 1993)
The present system of Technical Education was Introduced in India during the period of British rule and was generally patterned on the system existing in the western countries . In the year 1947, when the country got independence, there were in the entire country 38 institutions with an admission capacity of 2940, offering degree Programmes in engineering and technology. In case of technician education the corresponding figures were 52 institutions with an annual intake of 3670 students.